RANCANG BANGUN COLLABORATIVE SYSTEM PEMASARAN HOTEL SECARA ON-LINE DENGAN PENDEKATAN MEDIATOR BASED - Julian Supardi; Vebri Dores (Universitas Sriwijaya, 2009)
One important aspect of the development of information and communication technology in the economic field is marketing through the Internet. The development of marketing through the Internet network since the last decade very rapidly. Transactions that occur very tempting. That's why up a snowball effect, thus attracting businesses to leverage the Internet as a new marketing channels. This research was conducted to develop a marketing medium collaborative hotels. The approach used mediatore based. The methodology used in this collaborative media development is waterfall with steps Analysis, design, coding and testing. The results of this research is a collaborative media hotel marketing on-line has been implemented according to specifications that have been formulated in the SRS.Key words: Information technology, marketing collaborative, Mediatorbase